Statistical visualization of the Earth's magnetotail and the implied mechanism of substorm triggering based on superposed-epoch analysis of THEMIS data - S. Machida (Annales Geophysicae, 2014)
To investigate the physical mechanism responsible for substorm triggering, we performed a superposed-epoch analysis using plasma and magnetic-field data from THEMIS probes. Substorm onset timing was determined based on auroral breakups detected by all-sky imagers at the THEMIS ground-based observatories. We found earthward flows associated with north–south auroral streamers during the substorm growth phase. At around X = −12 Earth radii (RE), the northward magnetic field and its elevation angle decreased markedly approximately 4 min before substorm onset. Moreover, a northward magnetic-field increase associated with pre-onset earthward flows was found at around X = −17 RE. This variation indicates that local dipolarization occurs. Interestingly, in the region earthwards of X = −18 RE, earthward flows in the central plasma sheet (CPS) reduced significantly approximately 3 min before substorm onset, which was followed by a weakening of dawn-/duskward plasma-sheet boundary-layer flows (subject to a 1 min time lag). Subsequently, approximately 1 min before substorm onset, earthward flows in the CPS were enhanced again and at the onset, tailward flows started at around X = −20 RE. Following substorm onset, an increase in the northward magnetic field caused by dipolarization was found in the near-Earth region. Synthesizing these results, we confirm our previous results based on GEOTAIL data, which implied that significant variations start earlier than both current disruption and magnetic reconnection, at approximately 4 min before substorm onset roughly halfway between the two regions of interest; i.e. in the catapult current sheet.